Tinjauan Peran Ibu Rumah Tangga Presfektif Perekonomian Domestik dan Global - Muhammad Faqihudin (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2019)
Being a housewife is a very big gift for a woman. This gift if used optimally will be a good deed not only in the world but also in the hereafter. However, there are some women who misunderstood the nature so that he took off his responsibilities as a housewife, the principle matters as housewives were abandoned for various reasons including economic reasons. In economic terms, it actually still has room to participate in the global and domestic economy within the boundaries which are certainly not as broad and free as men. This study aims to further explore the role of housewives in domestic and global economics in a qualitative way, in the hope of producing findings that can be useful as needed.